Within- and between-host dynamics of producer and non-producer pathogens - Pike, V; Stevens, E; Griffin, A; King, KC (Cambridge University Press, 2023)
For infections to be maintained in a population, pathogens must compete to colonise hosts and transmit between them. Within the host, much research has been conducted into pathogeni interactions, yet less is known about whether within-host interactions can affect between-host transmission. In this study, we use an experimental approach to investigate within-and-between host dynamics using the pathogen Pseudomonas aeruginosa and the host Caenorhabditis elegans. Within-host interactions often involve the production of goods, that are beneficial to all the pathogens in the local environment but susceptible to exploitation by non-producers. We exposed the nematode host to ‘producer’ and two ‘non-producer’ bacterial strains (specifically for siderophore production and quorum sensing), in single infections and coinfections, to investigate within-host colonisation. Subsequently, we introduced infected nematodes to pathogen-naive populations, to allow natural pathogen transmission between hosts. We find that producer pathogens are consistently better at colonising hosts and transmitting between them than non-producers during coinfection and single infection. Non-producers were poor at colonising hosts and between-host transmission, even when coinfecting with producers. Understanding pathogen dynamics across these multiple levels will ultimately help us to predict and control the spread of infections and contribute to explanations for the persistence of cooperative genotypes in natural populations.